Pipeline Policy of Kazakhstan in the Caspian Region - Lidiya Andreyevna Parkhomchik (Проблемы постсоветского пространства)
The article considers promising development trends for oil and gas infrastructure in the country, as well as defines problem issues of existing pipelines using. At this point, the author notes that the key values for subsequent increase of transport and logistics facilities in Kazakhstan are both implementation of the multi-vector policy in the sphere of pipeline routes diversification and targeted development of cooperation with foreign partners in the oil and gas industry. The article also notes that the geopolitical features of the Caspian region have a direct impact on the formation of country’s strategic course the in the field of pipeline transport.